Clients' Satisfaction towards Indian Veterinary Research Institute- Referral Veterinary Polyclinic Services: A Case Study - Biam, Kamni P; Chander, Mahesh; Paul, Pampi (Indian Journal of Extension Education, 2022)
The study was conducted at Indian Veterinary Research Institute- Referral Veterinary Polyclinic (RVP), Izatnagar, to assess the clients' satisfaction on the overall veterinary service provided by the polyclinic from 2019-2020. A total of 60 clients visiting the RVP were at random selected irrespective of the animal they brought and place they belong to. 95 per cent of the clients prefer IVRI-RVP over other private or government-run clinics because of nominal consultation fees, and 93.33 per cent due to their belief in the Institute's reliability of treatment of the diseases diagnosed on their animals. All the clients agreed that the IVRI-RVP cleanliness was very satisfactory; 98.33 percent of them felt that the veterinarians were courteous and genuinely concerned for their animals, and clearly explained their problems upon diagnosis. 56.67 per cent of the clients rated the overall quality of veterinary services as very good and were more than happy to recommend the polyclinic to their families and friends.